Pengaruh Sales Growth, Asset Structure dan Liquidity Terhadap Capital Structure - Safitri, Nadia; Lamsah, Lamsah (Media Akuntansi Perpajakan, 2025)
The purpose of this research is to analyze to determine the effect of sales growth, asset structure, and liquidity on capital structure. The research method used is quantitative. The data used in this study is secondary data. The population in this study is plantation sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample selection method was purposive sampling. Based on this method, 10 sample companies were obtained with a research period of 5 years, resulting in a total of 50 audited research samples. Data processing was tested using IBM Statistical Package for the Social Sciences (SPSS) version 27. The results of the partial test (t-test) in this study indicate that sales growth partially has no effect on capital structure. Asset structure partially has a significant effect on capital structure. Liquidity partially has no effect on capital structure. Meanwhile, the results of the simultaneous test (f-test) in this study indicate that sales growth, asset structure, and liquidity simultaneously have a significant effect on capital structure. This study aims to contribute to capital structure by presenting the latest empirical evidence in the plantation sector and becoming a consideration for company management in making funding decisions, as well as providing recommendations for investors and other stakeholders regarding the company's financial condition